PENGETAHUAN DAN STIGMA TERHADAP PASIEN HIV/AIDS DI LINGKUNGAN KESEHATAN, INDONESIA - Siti Urifah (Universitas Muhammadiyah Jember, 2017)
Background: Lack of knowledge and misunderstanding about HIV transmissioncan influence the attitude toward patients with HIV or AIDS among health care providers. Negative attitude or stigmatizing attitude toward HIV or AIDS patients can create barriers to the provision of quality care. In healthcare settings in In- donesia, nurses are the majority group of health personnel. Thus, lack of knowledge about HIV transmission and poor attitudes of nurses may result in poor health care services for these patients. This study to examine the stigmatizing attitude and knowledge about HIV transmission among nurses in Indonesia Methods: A cross sectional study was conducted with 400 nurses providing care to patients with HIV or AIDS in eight public hospitals in Jakarta selected by using convenience sampling method. Knowledge about HIV transmission was measured by using Knowledge of HIV/AIDS questionnaire, and Provider Attitude Toward PLHIV questionnaire was used to assess nurses’ stigmatizing attitude toward patients with HIV or AIDS. Data were analyzed by frequency, percentage, mean, standard deviation, and Pearson correlation. Results: The results of this study showed that approximately 17.5 % of nurses had poor knowledge about HIV transmission. Among all nurses in this study, 27.7 % and 40.0 % of them answered that sweat and urine can transmit HIV, respectively. It was found that only 24.3 % of the nurses had a good attitude toward patients with HIV or AIDS. More than half of the nurses agreed and strongly agreed that patients with HIV or AIDS should be isolated and that hospital facilities for these patients must be kept separate from other facilities. Moreover, 28.8% of the nurses believed that HIV and AIDS was punishment from God. In addition, this study also revealed that there was a significantly negative correlation between knowledge about HIV transmission and stigmatizing attitude toward patients with HIV and AIDS patients (r = -.171, p .01). This finding revealed that the nurses who had poor knowledge about HIV transmission were more likely to have stigmatizing attitude toward HIV/AIDS patients. Conclusion: It is important for nurses to have accurate information about care for patients with HIV or AIDS patients and knowledge about HIV transmission. The results of this study suggested that knowledge about HIV transmission is still needed for nurses in Jakarta. Therefore, continuing education and training related to HIV and AIDS should be implemented in hospitals to enhance nurses’ HIV and AIDS knowledge, so that they can provide quality nursing care to patients with HIV or AIDS in the hospitals.Keywords: Knowledge, Stigmatizing Attitude, HIV/AIDS Patients, Nurses